Philosophy of national integration - "Gajendragadkar, P. B." (Delhi, 1974)
This is a lecture delivered by Dr. P B Gajendragadkar, Former Chief Justice of India and Chairman of the Law Commission on the occasion of Third Jawaharlal Nehru Memorial Lecture organized by Institute of Constitutional and Parliamentary Studies.
Keywords: Nationalism